Discovery of non-electrophilic capsaicinoid-type TRPA1 ligands. Issue 5 (1st March 2015) - Del Prete, Danilo; Caprioglio, Diego; Appendino, Giovanni; Minassi, Alberto; Schiano-Moriello, Aniello; Di Marzo, Vincenzo; De Petrocellis, Luciano
Graphical abstract: Abstract: Replacement of the benzylamide motif of synthetic capsaicin (nonivamide, 1c ) with a tetrazole moiety was detrimental for TRPV1 binding, but unexpectedly generated a potent and non-electrophilic TRPA1 agonist (4a ). Spurred by this observation and by the relatively small number of non-covalent TRPA1 ligands reported so far, the benzylamide-to-tetrazole swap was investigated in the more lipophilic and powerful vanilloids olvanil (1d ), rinvanil (1e ), and phenylacetylrinvanil (1f ). In all cases, the replacement was detrimental for TRPV1 binding, but a clear modulation of TRPA1 activity was observed. These observations show that the capsaicinoid pharmacophore displays orthogonal structure–activity relationships for TRPV1 and TRPA1 binding, and suggest the possibility of obtaining compounds with dual TRPV1/TRPA1 modulatory properties by exploration of the chemical space around the capsaicin motif.